(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This paper addresses the theatrical conception proposed by Semente Cia. de Teatro, based on a scenic approach that seeks to sacralize the theatrical activity through the incorporation of elements from Candomblé into the dramaturgical diegesis. In two productions, a scenic embodiment is proposed in which actors and actresses become “vessels” for their characters. This Terreiro Theatre proposal serves as a simulacrum, akin to the Deus Ex Machina in Greek theatre, and brings to the stage caboclos, padês, ayós, ogãs with their atabaques, alongside references to terreiro aesthetics. The group works with the body-orality of the actors and actresses, respecting the gestural and sensual grammar that constitutes the corporeal language of Black identity.